IMPREGNASI DAN KARAKTERISASI K-DEOILED SPENT BLEACHING EARTH (K-DSBE) DENGAN METODE BASAH - Arif Dwiki Saputra; Noor Hindryawati; Daniel Daniel (JURNAL KIMIA MULAWARMAN, 2018)
In this research, KOH has been impregnated on Deoiled Spent Bleaching Earth (DSBE) with wet method as a catayst. KOH was impregnated on DSBE of 40 % and 60 % (w/w), then characterized using X-Ray Flourescence (XRF), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), surface area test and alkalinity test. The XRF analysis results showed that potassium oxide composition increased after impregnation. The XRD analysis results show that DSBE belongs to the rectorite type of Na-montmorillonite, whereas the SEM analysis results indicate a morphological change in DSBE. K-DSBE catalysts 40 % and 60 % KOH impregnation have a basicity of 1.46 mmol/g and 1.55 mmol/g with a surface area of ​​23.81 m2/g and 23.56 m2/g.